Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve for the coefficient [tex]\( b \)[/tex] in the standard form of the quadratic function [tex]\( f(x) = ax^2 + bx + c \)[/tex], we start by creating a system of equations using the given points on the function. We will use three points to create our equations.
The points given are:
- (-4, 7)
- (-3, 6)
- (-2, 7)
Using these points, we can write out the following system of equations:
1. For [tex]\( x = -4 \)[/tex] and [tex]\( f(x) = 7 \)[/tex]:
[tex]\[ a(-4)^2 + b(-4) + c = 7 \][/tex]
This simplifies to:
[tex]\[ 16a - 4b + c = 7 \][/tex]
2. For [tex]\( x = -3 \)[/tex] and [tex]\( f(x) = 6 \)[/tex]:
[tex]\[ a(-3)^2 + b(-3) + c = 6 \][/tex]
This simplifies to:
[tex]\[ 9a - 3b + c = 6 \][/tex]
3. For [tex]\( x = -2 \)[/tex] and [tex]\( f(x) = 7 \)[/tex]:
[tex]\[ a(-2)^2 + b(-2) + c = 7 \][/tex]
This simplifies to:
[tex]\[ 4a - 2b + c = 7 \][/tex]
Now we have the following system of linear equations:
[tex]\[ \begin{cases} 16a - 4b + c = 7 \\ 9a - 3b + c = 6 \\ 4a - 2b + c = 7 \end{cases} \][/tex]
To solve for [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex], we can first eliminate [tex]\( c \)[/tex]. Subtract the second equation from the first equation:
[tex]\[ (16a - 4b + c) - (9a - 3b + c) = 7 - 6 \][/tex]
Simplifies to:
[tex]\[ 7a - b = 1 \quad \text{(Equation 4)} \][/tex]
Next, subtract the third equation from the second equation:
[tex]\[ (9a - 3b + c) - (4a - 2b + c) = 6 - 7 \][/tex]
Simplifies to:
[tex]\[ 5a - b = -1 \quad \text{(Equation 5)} \][/tex]
Now, we have two simpler equations to solve:
[tex]\[ \begin{cases} 7a - b = 1 \\ 5a - b = -1 \end{cases} \][/tex]
Subtract the fifth equation from the fourth equation to eliminate [tex]\( b \)[/tex]:
[tex]\[ (7a - b) - (5a - b) = 1 - (-1) \][/tex]
This simplifies to:
[tex]\[ 2a = 2 \][/tex]
Solving for [tex]\( a \)[/tex], we get:
[tex]\[ a = 1 \][/tex]
Substitute [tex]\( a = 1 \)[/tex] back into Equation 4:
[tex]\[ 7(1) - b = 1 \][/tex]
Simplifies to:
[tex]\[ 7 - b = 1 \][/tex]
Solving for [tex]\( b \)[/tex], we get:
[tex]\[ b = 6 \][/tex]
Thus, the value of [tex]\( b \)[/tex] is:
[tex]\[ \boxed{6} \][/tex]
The points given are:
- (-4, 7)
- (-3, 6)
- (-2, 7)
Using these points, we can write out the following system of equations:
1. For [tex]\( x = -4 \)[/tex] and [tex]\( f(x) = 7 \)[/tex]:
[tex]\[ a(-4)^2 + b(-4) + c = 7 \][/tex]
This simplifies to:
[tex]\[ 16a - 4b + c = 7 \][/tex]
2. For [tex]\( x = -3 \)[/tex] and [tex]\( f(x) = 6 \)[/tex]:
[tex]\[ a(-3)^2 + b(-3) + c = 6 \][/tex]
This simplifies to:
[tex]\[ 9a - 3b + c = 6 \][/tex]
3. For [tex]\( x = -2 \)[/tex] and [tex]\( f(x) = 7 \)[/tex]:
[tex]\[ a(-2)^2 + b(-2) + c = 7 \][/tex]
This simplifies to:
[tex]\[ 4a - 2b + c = 7 \][/tex]
Now we have the following system of linear equations:
[tex]\[ \begin{cases} 16a - 4b + c = 7 \\ 9a - 3b + c = 6 \\ 4a - 2b + c = 7 \end{cases} \][/tex]
To solve for [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex], we can first eliminate [tex]\( c \)[/tex]. Subtract the second equation from the first equation:
[tex]\[ (16a - 4b + c) - (9a - 3b + c) = 7 - 6 \][/tex]
Simplifies to:
[tex]\[ 7a - b = 1 \quad \text{(Equation 4)} \][/tex]
Next, subtract the third equation from the second equation:
[tex]\[ (9a - 3b + c) - (4a - 2b + c) = 6 - 7 \][/tex]
Simplifies to:
[tex]\[ 5a - b = -1 \quad \text{(Equation 5)} \][/tex]
Now, we have two simpler equations to solve:
[tex]\[ \begin{cases} 7a - b = 1 \\ 5a - b = -1 \end{cases} \][/tex]
Subtract the fifth equation from the fourth equation to eliminate [tex]\( b \)[/tex]:
[tex]\[ (7a - b) - (5a - b) = 1 - (-1) \][/tex]
This simplifies to:
[tex]\[ 2a = 2 \][/tex]
Solving for [tex]\( a \)[/tex], we get:
[tex]\[ a = 1 \][/tex]
Substitute [tex]\( a = 1 \)[/tex] back into Equation 4:
[tex]\[ 7(1) - b = 1 \][/tex]
Simplifies to:
[tex]\[ 7 - b = 1 \][/tex]
Solving for [tex]\( b \)[/tex], we get:
[tex]\[ b = 6 \][/tex]
Thus, the value of [tex]\( b \)[/tex] is:
[tex]\[ \boxed{6} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.